Greenland- Scotland Overflow studied by hydro-chemical multivariate analysis - Fogelqvist, E; Blindheim, J.; Tanhua, Toste; Buch, E.; Österhus, S. (Deep Sea Research Part I: Oceanographic Research Papers, 2003)
Hydrographic, nutrient and halocarbon tracer data collected in July–August 1994 in the Norwegian Sea, the Faroe Bank Channel (FBC), the Iceland and Irminger Basins and the Iceland Sea are presented. Special attention was given to the overflow waters over the Iceland–Scotland Ridge (ISOW). The Iceland–Scottland overflow water (ISOW) was identified along its pathway in the Iceland Basin, and entrainment of overlying water masses was quantified by multivariate analysis (MVA) using principal component analysis (PCA) and Partial Least Square (PLS) calibration. It was concluded that the deeper portion of the ISOW in the FBC was a mixture of about equal parts of Norwegian Sea Deep Water (NSDW) and Norwegian Sea Arctic Intermediate Water (NSAIW). The mixing development of ISOW during its descent in the Iceland Basin was analysed in three sections across the plume. In the southern section at 61°N, where the ISOW core was observed at Full-size image (<1 K) depth, the fraction of waters originating north of the ridge was assessed to be 54%. MVA assessed the fractional composition of the ISOW to be 21% NSDW, 22% NSAIW, 18% Northeast Atlantic Water (NEAW), 11% Modified East Icelandic Water, 25% Labrador Sea Water (LSW) and 3% North East Atlantic Deep Water. It may be noted that the fraction of NEAW is of the same volume as the NSDW. On its further path around the Reykjanes Ridge, the ISOW mixed mainly with LSW, and at 63°N in the Irminger Basin, it was warmer and fresher (θ=2.8°C and S=34.92) than at 61°N east of the ridge Full-size image (<1 K). The most intensive mixing occurred immediately west of the FBC, probably due to high velocity of the overflow plume through the channel, where annual velocity means exceeded Full-size image (<1 K). This resulted in shear instabilities towards the overlying Atlantic waters and cross-stream velocities exceeding Full-size image (<1 K) in the bottom boundary layer. The role of NSAIW as a component of ISOW is increasing. Being largely a product of winter convection in the ...